Effect of NaCl addition on alcohol-alkali-treated waxy rice starch: Structural and physicochemical functionality. (30th September 2022) - Huang, Yanxia; Bao, Xianyang; Li, Pan; Zhan, Lei; Wu, Hai; Chen, Pei
Graphical abstract: Highlights: NaCl increased apparent viscosity, dynamic modulus values of waxy rice starch (WRS) and alcohol-alkali-treated waxy rice starch (AAT-WRS). Textural paraments of WRS were positively correlated to NaCl content. FT-IR results indicated NaCl could increase the degree of short-range order of WRS and AAT-WRS. SEM images revealed that NaCl wrapped up the surface of starch granules. Abstract: The physicochemical and structural properties of waxy rice starch (WRS) and alcohol-alkali-treated waxy rice starch (AAT-WRS) were determined in the presence of different concentrations of NaCl (0, 2, 4, 6 and 8%). The results showed that NaCl decreased the transparency of WRS and AAT-WRS pastes, but enhanced both freeze–thaw stability and apparent viscosity (p < 0.05). The rheological measurement results showed that the addition of NaCl could improve the modulus values of both WRS and AAT-WRS, and the effect on WRS was more significant than that on AAT-WRS. The textural parameters of WRS pastes were evidently enhanced by NaCl, but the presence of NaCl had no significant effect on the firmness of AAT-WRS pastes. The results of SEM and FT-IR revealed that NaCl could protect the granular morphology and increase the degree of short-range order of WRS and AAT-WRS.